A scalable chemical vapor deposition synthesis of high purity hollow carbon onions. (May 2020) - Ruan, Chao; Li, Zhigang; Zhang, Dou; Yuan, Xinxin; Liang, Chen; Chang, Yi; Huang, Hailu; Xu, Lele; Chen, Minghai
Abstract: Carbon onions have shown potential applications in many fields due to their low density, tunable conductivity, excellent thermal and chemical stability. In this study, we report an efficient method for synthesis of gram-scale hollow carbon onions (HCNOs). A chemical vapor deposition (CVD) process was carried out at 700 °C with magnesium oxide supported cobalt as catalyst. Abundant HCNOs were obtained by leaching the CVD product in hydrochloric acid when the precursor weight ratio of cobalt and magnesium oxide is 5%. Scanning electron microscopy and transmission electron microscopy images indicate the sample is composed of hollow polyhedral particles with diameter of 10–50 nm. The thermogravimetric analysis indicates the purity of HCNOs is about 99%. X-ray diffraction and Raman spectra demonstrates a moderate graphitization of HCNOs in which graphite carbon and defective carbon both present. The graphite carbon can provide good conduction that is beneficial to introduce the microwave, while the defects can provide abundant polarization center to stimulate the formation of multiple dielectric resonances. The calculated reflection loss curve of HCNOs with a thin thickness of 2 mm exhibit wide absorption bandwidth at high frequency (13.5–16.9 GHz), indicating an excellent microwave absorption performance at high frequency. Graphical abstract: Image 10171